Power Testing in Basketball: Current Practice and Future Recommendations. Issue 9 (September 2018) - Wen, Neal; Dalbo, Vincent J.; Burgos, Bill; Pyne, David B.; Scanlan, Aaron T.
Abstract : Abstract: Wen, N, Dalbo, VJ, Burgos, B, Pyne, DB, and Scanlan, AT. Power testing in basketball: Current practice and future recommendations. J Strength Cond Res 32(9): 2686–2700, 2018—Numerous foundational movements performed during basketball are predicated on underlying power-related attributes, including speed, change-of-direction (COD), and jumping. Accordingly, fitness testing batteries for basketball have incorporated an assortment of linear speed tests, COD tests, and jump tests. However, because of the wide variety of testing options, it is difficult for basketball practitioners to select appropriate testing protocols for the assessment of power-related attributes. As a result, there is a need to review the relevant literature to identify game-specific, power-related attributes important in basketball and the most appropriate tests available to assess power-related attributes for basketball practitioners. Therefore, the aims of this review were to: (a) identify essential power-related attributes important in basketball; (b) discuss the suitability of common and novel power-related tests; and (c) provide recommendations for future research and best practice approaches for basketball coaching staff. In this review, we propose a series of novel tests that are more targeted and specific to basketball movements including: (a) 5- and 10-m linear sprints, (b) modified agility T-test, (c) change-of-direction deficit (CODD), (d) lateral bound, (e) Sargent jump, (f) one-step jump, and (g) isometric midthigh pull test. Improved testing of power-related attributes should enable basketball practitioners to develop targeted training plans for enhancing player performance.